(untitled) (Research, Society and Development, 2022)
Soil quality is directly related to the diversity and density of microorganisms present in it, as they perform important functions that promote the growth of plant species, maintaining soil sustainability and favoring increased agricultural production and environmental regeneration. With this, the objective was to describe and relate the functions of microorganisms existing in the soil and their action potentials in agricultural and forestry species. Some species of fungi and bacteria are able to solubilize phosphorus from phosphate sources, releasing it to be absorbed by plant roots, resulting in gains in crop productivity. Other species of bacteria, when inoculated to seeds, besides stimulating the growth and development of plants, act as biofertilizers by fixing nitrogen from the air (N2). Mycorrhizae constitute a specialized symbiotic association between roots and some soil fungi in which fungal hyphae absorb nutrients from the soil solution and transport them to plants. The inoculation of plant species with microorganisms that help in the availability of phosphorus, due to its low concentration in soils, becomes essential in supplying the nutritional demands of plants and arbuscular mycorrhizal fungi (AMF) and phosphate solubilizing bacteria are among microorganisms that can perform this function. In relation to the main forest species cultivated in Brazil, all have the potential to benefit from associations with microorganisms, hence the importance of knowing, researching and stimulating the increase of the microbial quality of the soil.